HUMAS PEMERINTAH DI ERA INTEGRASI ARTIFICIAL INTELLIGENCE: STUDI PRAKTISI IPRA HUMAS JAWA TIMUR - Rachmawati, Farikha; Finaliyani Putri , Dhelittya (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
The integration of Artificial Intelligence (AI) has generated significant transformations in government public relations practices in Indonesia. This study aims to examine how AI is utilized, conceptualized, and integrated by government public relations practitioners affiliated with IPRA Humas East Java. Specifically, the study explores the maturity levels of AI adoption, the shifting roles of public relations professionals, emerging ethical and professional challenges, and the readiness of human resources in responding to technological transformation. This research employs a qualitative explanatory approach using Focus Group Discussions (FGDs) with public relations practitioners from various regional government institutions. The data were analyzed through the Miles, Huberman, and Saldaña qualitative analytic framework, involving processes of data condensation, data display, and conclusion drawing/verification. The findings indicate that AI integration within government public relations remains uneven across institutions. Most practitioners employ AI primarily at the level of technical automation, including content creation, voice-over production, visual design, and idea generation. Several institutions have advanced toward big data–driven applications such as media monitoring and sentiment analysis, while only a limited number have adopted AI as a tool for supporting strategic communication. Additional findings reveal the existence of an inter-institutional “AI readiness gap,” the emergence of FOMO-driven AI adoption, limited digital literacy, and concerns related to ethics, information accuracy, and data security. The study proposes a Hybrid Human–AI Government PR Practice model as a more adaptive framework for guiding public relations work within the evolving landscape of technological integration.. Keywords: Government Public Relations, Artificial Intelligence, IPRA Humas Jatim, Excellence Theory